How physical activity and passion color the passage of time: A response with ultra-trail runners - Hallez, Quentin; Paucsik, Marine; Tachon, Guillaume; Shankland, Rebecca; Marteau-Chasserieau, Fanny; Plard, Mathilde (Frontiers in Psychology, 2023)
The aim of this study was to replicate the results of a lengthening effect caused by physical activity already observed in duration length judgment, using the time passage judgment measure, while exploring the effects of passion types (obsessive vs. harmonious) on time perception. A total of 378 ultra-trail runners responded to an online questionnaire in which the type of passion and the passage of time (PoT) judgments associated with both an ultra-trail context and a non-trail daily context were collected. The results showed that participants systematically judged the time as being dilated in a situation of sports practice, thus extending the results obtained in interval duration judgment studies. This study also showed an influence of the type of passion: higher levels of harmonious passion were related to greater feelings of time dilation, while higher levels of obsessive passion were related to greater feelings of both time contraction and time dilation. Results are discussed in light of the two major factors that influence the PoT referenced in the literature, namely, attention and happiness level.